Postharvest losses of fruit and vegetables and their financial impacts on retail in the Municipality of Chapadinha, Maranhão (Research, Society and Development, 2020)
Even though Brazil has a great diversity of production and commercialization of horticulture, the country still faces a series of factors that limit the efficiency of distribution and commercialization, being postharvest losses one of the most important, reflecting in high socioeconomic impacts in the productive chain. The objective of this work was to evaluate the postharvest losses of vegetables and fruits and their impacts on the retail trade in the municipality of Chapadinha. The research was developed through interviews with marketers and retailers who sell fruit and vegetables in the city of Chapadinha, Maranhão, from August to December 2019. A questionnaire consisting of 30 questions was used, covering socioeconomic, marketing and? The losses of vegetables and fruits were calculated using the average quantity purchased/week and the average quantity sold/week. Among vegetables, it was found that eggplant recorded the highest rate of loss. Among fruits, the greatest losses were seen in watermelon and pineapple. The main reasons are the lack of hygiene, inadequate positioning of products and the presence of animals. It was observed that postharvest losses reduced the profit of traders by up to 23.27%, causing a great impact on the accounts of the establishment. It is suggested to adopt practices related to the handling, hygiene, transport and storage of products, which can be acquired through training and technical guidance from a qualified professional (agronomist and / or agribusiness technician).